Undergraduates' perception on ethics and integrity in the construction sector - Abdul Rashid, Khairuddin (2008)
This paper concerns ethics and integrity in the construction sector. The objective of the paper is to report the outcome of a study among construction undergraduates on their perception on ethics and integrity in the Malaysian construction sector. The findings of the study suggest that un-ethical practices are present in the construction sector and the sector lacks integrity. In addition, the findings indicated that some undergraduates have the inclination to be involved in un-ethical practices in the future. Furthermore the study identified the areas and parties most likely to be susceptible to un-ethical practices and the key reasons why the construction sector lacks integrity. The paper concludes by suggesting that further and in-depth studies are required to identify and to address issues on ethics and integrity in the construction sector of Malaysia.